Análise da abrangência semântica e formal do desempenho estratégico esperado com a implantação da educação corporativa em uma organização do setor bancário - Carvalho, Luciano Martins de (2013)
This work is inserted on the studies field of strategy and its aims to contribute to the comprehension of how the strategic performance has been worthy and measured by the Organizations. For both, it was made an analysis of the semantic and formal comprisement of the strategic performance with the corporative educacional implantation on a bank segment organization. On the theoretical framework were inicialy presented the concepts of the strategic performance, corporative performance, ways of strategic performance and, finally, on a multidimensional model of analysis of the concept of performance that served as the basis to the analysis. After it, there were presented some subjects: the corporative education, corporative education in the development of the competences and the corporative university. The corporative education, having as its representative element the corporative university, was chosen to be the base to data analysis as it represents an strategic choice the Organizations, it means, it is considered by the literature of the field as one of the ways to reach the competitive advantage and guarantee the business perennial. This way, the results of the implementation may be included on the multidimensional analysis of the company´s performance, viewing the comprehension of the concept and operationalization of the strategic performance.The Bradesco Bank was the chosen company to this study, as it recently has implemented a corporative university. The methodology used was a study of an unique case with data collection of secundary nature by means of documental analysis of the implementation project of the corporative university Bradesco, and through of reports from the several teams that composed the project and informal consultants regarding the specific issues with the leaders of the teams and other areas of the Bradesco Corporative University. After this process, the collected datas were submited to a contents analysis, based on the dimensions and properties of the multidimensional model of analysis of the concept performance. As a result of the study, it was identified the semantic and formal comprisement of the strategic performance aimed by means of the Bradesco´s Corporative University, in agreement with the analysis of the proposed model on this research. Amongst the discoveries, we call the attention to the following: the concern of the organization with the measurement of the multidimensional performance concept and, consequently, the expanded performance conceptualization, considering that the results of the corporative education will have a direct impact in several of results areas and in a cumulative way.